Focal dermal hypoplasia: a case report and review of literature (2003)
A 14 year old girl was seen in the clinic with a huge vulvar wart, and warts on both tonsils. She also had poikiloderma. She had bony abnormalities, which included lobster claw abnormality of the right foot, a right cervical rib, and the right clavicle was lower than the left. There were fine parallel vertical radio-opaque lines in the distal femoral tibial metaphyses bilaterally (osteopathla striata). A diagnosis of Focal dermal hypoplasia was made. The huge vulvar wart and the warts on the tonsils were excised. She recovered promptly and she was discharged home.